Transvesical endoscopic peritoneoscopy: intra-abdominal scarless surgery for urologic applications - Lima, Estêvão Augusto Rodrigues de (2008)
For many abdominal procedures, advantages such as minimal scarring, reduced pain, and faster recovery have made laparoscopy the favored approach over traditional open surgery. The most recent minimally invasive approach is natural orifice transluminal endoscopic surgery (NOTES), which limits morbidity because this surgery does not require incision. This article reviews the history, development, and current and future applications of NOTES in the field of urology.